Time as a Research Lens: A Conceptual Review and Research Agenda - Blagoev, Blagoy; Hernes, Tor; Kunisch, Sven; Schultz, Majken (Journal of Management, 2024)
Time is gaining recognition as an important research perspective, yet the assumptions, concepts, and boundaries of this perspective vary greatly across different fields. This diversity suggests that time offers both significant depth and relevance as a lens for research. However, the diversity of approaches also harbors ambiguity and a lack of coherence, hindering scholars’ ability to integrate insights and harness the full potential of time as a research lens. To address this issue, we review the diverse time-based assumptions, domains, and concepts in extant research. Our review reveals three dominant manifestations of the temporal lens: time as resource, time as structure, and time as process. We analyze and synthesize insights of the three lenses to offer an integrative framework to support future research. The framework informs and reveals opportunities for time-based research by foregrounding connections and contrasts among the lenses. Building on this framework, we discuss two principal pathways for future research: connecting the three lenses through the study of tensions at their interfaces, and enhancing the three lenses through the study of more complex conceptions of time.